Synthesis of chiral α-hydroxy acids via palladium-catalyzed C(sp3)–H alkylation of lactic acid. Issue 9 (18th December 2015) - Chen, Kai; Li, Xin; Zhang, Shuo-Qing; Shi, Bing-Feng
Abstract : A palladium-catalyzed alkylation of lactic acid with alkyl iodides is described. Abstract : Herein we report a Pd-catalyzed alkylation of lactic acid with the assistance of 8-aminoquinoline auxiliary. A wide range of alkyl iodides bearing β-hydrogen atoms are compatible with the reaction conditions, providing a practical and straightforward alternative to access chiral α-hydroxy acids (AHAs). The new reactions have been applied for the synthesis of isotope-labeled AHAs and a sugar-containing complex AHA.